Dry-land resistance training practices of elite swimming strength and conditioning coaches - Crowley, E.; Harrison, A. J.; Lyons, M. (The Journal of Strength and Conditioning Research, 2018)
No research to date has investigated dry-land resistance (RT) training practices of elite swimming strength and conditioning coaches. This is the first comprehensive study exploring dry-land RT training practices in swimming. The aims of this study were to examine (a) the dry-land RT training practices and exercises used by elite swimming strength and conditioning coaches and (b) the rationale provided by coaches about their practices and prescription of specific dry-land RT training exercises. Twenty-three (n = 21 males, n = 2 females) elite swimming strength and conditioning coaches, from Ireland (n = 7), Great Britain (n = 5), Australia (n = 6), and the United States of America (n = 5) were recruited through their specific national governing bodies. Coaches completed an online questionnaire consisting of 7 sections; subject information, informed consent, coach's biography, coach education, current training commitments, dry-land RT training practices and exercises, and additional information. The results showed that coaches had varying levels of experience, education and worked with different level swimmers. A total of 95 dry-land RT training exercises were used by the coaches across 4 different dry-land RT training practices (warm-up, circuit training, traditional RT training and plyometrics). Traditional RT training (87%) was the most commonly practiced. The pull-up and squat were the most popular dry-land RT training exercises used by elite swimming strength and conditioning coaches. Future research needs to focus on exploring the specificity and the transfer of RT training exercises to swimming performance.